Understanding librarians' experiences of copyright: Findings from a phenomenographic study of UK information professionals. Issue 6 (15th August 2017) - Morrison, Chris; Secker, Jane
Abstract : Purpose: Librarians and information professionals increasingly need to deal with copyright issues in their work, however evidence suggests that they can lack confidence and often refer queries to a dedicated copyright specialist. The purpose of this paper is to explore the professional experiences of copyright of a group of academic librarians in the UK, with a view to devising appropriate copyright education strategies. Design/methodology/approach: The research was conducted using phenomenography, which is a qualitative approach from education. Data were collected though group interviews to explore the variation of experience. Four categories of description were devised which are placed in an outcome space. Findings: There were four qualitatively distinct ways that librarians experience copyright in their professional lives, including viewing it as a problem, as complicated, as a known entity and as an opportunity. The variations in experience relate to a variety of factors such as the librarians' role, ideology, level of experience, context and with whom they might be dealing. Originality/value: This is the first study of this nature, building on quantitative findings from a multinational survey. It concludes that librarians need to be taught about copyright in a way that acknowledges and addresses the challenges so that they can view it as empowering and as part of wider information literacy initiatives.